Tailored Lace: Moldless Fabrication of 3D Bio-Composite Structures through an Integrative Design and Fabrication Process - August Lehrecke; Cody Tucker; Xiliu Yang; Piotr Baszynski; Hanaa Dahy (Applied Sciences, 2021)
This research demonstrates an integrative computational design and fabrication workflow for the production of surface-active fibre composites, which uses natural fibres, revitalises a traditional craft, and avoids the use of costly molds. Fibre-reinforced polymers (FRPs) are highly tunable building materials, which gain efficiency from fabrication techniques enabling controlled fibre direction and placement in tune with load-bearing requirements. These techniques have evolved closely with industrial textile processes. However, increased focus on automation within FRP fabrication processes have overlooked potential key benefits presented by some lesser-known traditional techniques of fibre arrangement. This research explores the process of traditional bobbin lace-making and applies it in a computer-aided design and fabrication process of a small-scale structural demonstrator in the form of a chair. The research exposes qualities that can expand the design space of FRPs, as well as speculates about the potential automation of the process. In addition, Natural Fibre-Reinforced Polymers (NFRP) are investigated as a sustainable and human-friendly alternative to more popular carbon and glass FRPs.